Rehmannia glutinosa DC.-Lilium lancifolium Thunb. in the treatment of depression: a comprehensive review and perspectives - Wang, ZongHao; Wang, Xiaoyu; Mou, Xiangyu; Wang, ChangLin; Sun, Ya; Wang, JieQiong (Frontiers in Pharmacology, 2024)
Background: In recent years, the incidence of depression, recognized as a serious psychological disorder, has escalated rapidly. Rehmannia glutinosa DC. (Scrophulariaceae; Rehmanniae Radix, Crude drug ) and Lilium lancifolium Thunb. (Liliaceae; Lilii bulbus, Crude drug)constitute a classic anti-depressant combination, exhibiting pharmacological effects that include anti-depressive, anti-anxiety, and anti-inflammatory properties. Current clinical studies have demonstrated that Baihe Dihuang Decoction, a traditional Chinese herbal compound, is effective in treating depression. However, the majority of scholars have predominantly examined Rehmannia glutinosa and Lilium in isolation, and a comprehensive elucidation of their principal active metabolites and pharmacological mechanisms remains lacking. Methods: A comprehensive literature search was conducted as of September 29th, 2024, utilizing databases such as PubMed, CNKI, Wanfang Data, Baidu Scholar, and Google Scholar. Additionally, classical texts on Chinese herbal medicine, the Chinese Pharmacopoeia, as well as doctoral and master's theses, were included in the collected materials. The search employed specific terms including "Rehmannia glutinosa," "Lilium," "Baihe Dihuang decoction," "application of Baihe Dihuang decoction," "pathogenesis of depression," and "pharmacological action and mechanism of depression. Results: This paper reviewed the traditional applications and dosages of the Rehmannia glutinosa-Lilium as documented in Chinese medical classics, thereby establishing a foundation for the contemporary development and clinical application of the classical formula Baihe Dihuang Decoction. Additionally, recent years have seen a comprehensive review of the pharmacological effects and mechanisms of Rehmannia glutinosa-Lilium and its principal metabolites in the context of depression. Conclusion: This paper has reviewed the active metabolites of Rehmannia glutinosa-Lilium and demonstrated its efficacy in the treatment of depression, as well as its role in modulating the underlying mechanisms of the disorder. The findings aim to serve as a reference for further research into the mechanisms of depression, its clinical applications, and the development of novel therapeutic agents.